1999
DOI: 10.1046/j.1365-2443.1999.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of elongation factor 1α, an essential translational component, causes aberrant cell morphology by affecting the control of growth polarity in fission yeast

Abstract: Background: Elongation factor 1␣ (EF1␣), an essential component of the eukaryotic translational machinery, has been shown to possess various biochemical and biological activities, including F-actin-binding and -bundling, microtubulesevering, and the activity of making fibroblasts highly susceptible to transformation. However, our understanding of the biological significance of EF1␣ with respect to these various biochemical or biological activities remains limited. Here we report the identification of EF1␣-enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
19
1
Order By: Relevance
“…Polymerisation rates of uncapped filaments were reduced by ϳ70% with maximal deviance from the control curve occurring at 0.5 M. This indicates that ZmEF-1␣ is capable of decreasing monomer addition to the fast-growing barbed end of the actin filament. Although EF-1␣ has been reported to bind actin monomers, the affinity is far too low to account for the degree of polymerisation inhibition observed [Dharmawardhane et al, 1991;Murray et al, 1996;Suda et al, 1999]. The ZmEF-1␣ actin polymerisation inhibition observed here is qualitatively similar to that of barbed end capping proteins [Pollard and Cooper, 1986] such as gelsolin and capZ.…”
Section: Discussionmentioning
confidence: 48%
“…Polymerisation rates of uncapped filaments were reduced by ϳ70% with maximal deviance from the control curve occurring at 0.5 M. This indicates that ZmEF-1␣ is capable of decreasing monomer addition to the fast-growing barbed end of the actin filament. Although EF-1␣ has been reported to bind actin monomers, the affinity is far too low to account for the degree of polymerisation inhibition observed [Dharmawardhane et al, 1991;Murray et al, 1996;Suda et al, 1999]. The ZmEF-1␣ actin polymerisation inhibition observed here is qualitatively similar to that of barbed end capping proteins [Pollard and Cooper, 1986] such as gelsolin and capZ.…”
Section: Discussionmentioning
confidence: 48%
“…The interaction of eEF1A with actin was first identified in the slime mold Dictyostelium discoideum (Yang et al 1990). Using a combination of genetic and/or biochemical approaches, this ability of eEF1A to bind actin and promote actin bundling was demonstrated to be conserved in both budding (Munshi et al 2001) and fission yeast (Suda et al 1999). Subsequent genetic studies in S. cerevisiae enabled an analysis of the functional interaction between these two highly abundant proteins in vivo.…”
Section: Ribosomal Frameshiftingmentioning
confidence: 99%
“…In addition, another study indicated that high expression of eEF1A2 promoted cell migration, invasion, and metastasis through PTEN/PI3K/Akt pathway in breast cancer cells (Amiri et al 2007;Jimenez et al 2000;Xu et al 2013). Lastly, the ability of eEF1A2 to shorten microtubules and bind to F-actin (Li et al 2006) has raised the possibility that eEF1A2-derived cytoskeletal (Munshi et al 2001;Suda et al 1999) alterations might facilitate tumor formation.…”
Section: Fig 3 Continuedmentioning
confidence: 99%